2016
DOI: 10.1371/journal.pntd.0005221
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Case Detection for Plasmodium vivax Malaria Elimination in Rural Amazonia

Abstract: BackgroundMalaria burden in Brazil has reached its lowest levels in 35 years and Plasmodium vivax now accounts for 84% of cases countrywide. Targeting residual malaria transmission entrenched in the Amazon is the next major challenge for ongoing elimination efforts. Better strategies are urgently needed to address the vast reservoir of asymptomatic P. vivax carriers in this and other areas approaching malaria elimination.MethodsWe evaluated a reactive case detection (RCD) strategy tailored for P. vivax transmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 38 publications
2
40
0
Order By: Relevance
“…All study subjects lived in farming settlements in the Amazon Basin of Brazil, close to the border with Bolivia (Figure ). This area receives most rainfall between November and March (annual average, 2318 mm), but low‐level P vivax transmission occurs year‐round., with no P falciparum infections diagnosed since early 2012 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All study subjects lived in farming settlements in the Amazon Basin of Brazil, close to the border with Bolivia (Figure ). This area receives most rainfall between November and March (annual average, 2318 mm), but low‐level P vivax transmission occurs year‐round., with no P falciparum infections diagnosed since early 2012 …”
Section: Methodsmentioning
confidence: 99%
“…This area receives most rainfall between November and March (annual average, 2318 mm), but low-level P vivax transmission occurs year-round., with no P falciparum infections diagnosed since early 2012. 28,29…”
Section: Study Site and Participantsmentioning
confidence: 99%
“…Many studies evaluating the efficiency of RCD highlight its inability to halt infections in areas of low transmission due to the use of less sensitive RDTs, travel-related infections, and large budgetary requirements [2,18]. A major concern for RCD-based strategies is that asymptomatic individuals will be missed if no clinical cases report to CHWs [42]. A survey in coastal Kenya found that asymptomatic and symptomatic infections do not necessarily overlap spatially, and that clusters of symptomatic infections have greater temporal stability over more than ten years [42].…”
Section: Discussionmentioning
confidence: 99%
“…A major concern for RCD-based strategies is that asymptomatic individuals will be missed if no clinical cases report to CHWs [42]. A survey in coastal Kenya found that asymptomatic and symptomatic infections do not necessarily overlap spatially, and that clusters of symptomatic infections have greater temporal stability over more than ten years [42]. Another issue often highlighted is the different criteria and screening radii employed by countries to define and recruit neighbouring households [42] For example, RCD data from four villages in the Myanmar-Thailand border determined that RCD would only be successful at a radius of 150 metres, and any screening occurring beyond this radius would not perform better than random screening [2].…”
Section: Discussionmentioning
confidence: 99%
“…2,18 A major concern for RCD-based strategies is that asymptomatic individuals will be missed if no clinical cases report to CHWs. 42 A survey in coastal Kenya found that asymptomatic and symptomatic infections do not necessarily overlap spatially, and that clusters of symptomatic infections have greater temporal stability over >10 years. 42 Another issue often highlighted is the different criteria and screening radii employed by countries to define and recruit neighboring households.…”
Section: Discussionmentioning
confidence: 99%